The Presence of Psoriasis, Metabolic Syndrome and Their Combination Increases the Serum Levels of CRP and CD5L but Not sCD200R1 and sTLR2 in Participants - Holmannova, Drahomira; Borsky, Pavel; Andrys, Ctirad; Krejsek, Jan; Cermakova, Eva; Fiala, Zdenek; Hamakova, Kvetoslava; Svadlakova, Tereza; Párová, Helena; Rehacek, Vit; Poctova, Gabriela; Borska, Lenka (Journal of personalized medicine, 2022)
Psoriasis and metabolic syndrome (MetS) are chronic inflammatory conditions associated with the dysregulation of immune system reactivity. The inflammatory processes of both diseases have not yet been fully characterized, and the evaluation of proteins/markers that could be involved in their pathogenesis is of great importance. We selected four markers: CRP, sCD200R1, CD5L, and sTLR2; in particular, sCDR2001 has not yet been measured in the context of psoriasis and metabolic syndrome. Material and methods: In the study, 64 controls and 43 patients with psoriasis with or without a metabolic syndrome were enrolled. The levels of selected markers were measured using ELISA kits. Results: CRP levels were significantly higher in psoriasis patients, especially in the subgroup of patients with MetS compared to nonMetS patients (p < 0.01). sCD200R1 and sTLR2 were not significantly different between groups and subgroups; however, CD200R1 levels were slightly higher in both control groups compared to both groups of patients. CD5L levels were significantly higher in patients with MetS compared to nonMets patients (p < 0.02). We also evaluated the correlations between parameters in controls and patients' groups, as well as in subgroups. Correlations between BMI and CRP were found in all groups and subgroups. Other correlations were group- and subgroup-specific. For example, in the patients' group, CD5L correlated with sCD200R1 (p < 0.05) and in MetS controls, with age (p < 0.03). Conclusion: The results show that the presence of systemic inflammation associated with psoriasis and metabolic syndrome and their combination alters the expression of specific molecules, especially CRP and CD5L, which were significantly increased in patients with psoriasis and a metabolic syndrome compared to controls without metabolic syndromes. Correlations between CRP and BMI in all groups suggest that overweight and obesity increase the intensity of inflammation and potentiate CD5L expression. In contrast, levels of molecules that may limit inflammation were not increased in psoriasis and metabolic syndrome subjects (they were non-significantly lower compared with healthy controls), which may reflect the chronic nature of both diseases and the exhaustion of inhibitory mechanisms.